2023
DOI: 10.3390/fermentation9050447
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Functional Characterization of Acetic Acid Bacteria Isolated from Farm-Produced Fruit Vinegars

Abstract: Acetic acid bacteria (AAB) form a bacterial film on the surface of alcoholic solutions and ferment ethanol to acetic acid while also producing bioactive compounds. To discover functional AAB for industrial use, we isolated and selected strains from farm-produced vinegars using a CaCO3-containing medium. The seven isolated strains belonged to Acetobacter cerevisiae and Acetobacter pasteurianus. These strains were tolerant to ethanol concentrations up to 12% (v/v). Acidification was seen for GHA 7, GYA 23, JGB 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Negative correlations were found among ACE with vannilin (−0.95). Kim et al (2023) reported that most of the acetic acid bacteria isolated from eight vinegar samples had higher ACE inhibitory activity than the 0.1% captopril-positive control (76.9%) [34]. Similarly to the present study, Morgan et al (2016) observed the protective effect of apple cider vinegar on type II diabetes management [35].…”
Section: Antidiabetic and Antihypertensive Effectssupporting
confidence: 79%
See 2 more Smart Citations
“…Negative correlations were found among ACE with vannilin (−0.95). Kim et al (2023) reported that most of the acetic acid bacteria isolated from eight vinegar samples had higher ACE inhibitory activity than the 0.1% captopril-positive control (76.9%) [34]. Similarly to the present study, Morgan et al (2016) observed the protective effect of apple cider vinegar on type II diabetes management [35].…”
Section: Antidiabetic and Antihypertensive Effectssupporting
confidence: 79%
“…Negative correlations were found among ACE with vannilin (−0.95). reported that most of the acetic acid bacteria isolated from eight vinegar sampl had higher ACE inhibitory activity than the 0.1% captopril-positive control (76.9%) [34 Similarly to the present study, Morgan et al (2016) observed the protective effect of app cider vinegar on type II diabetes management [35]. The antidiabetic mechanism of ultr sound treatment in watermelon vinegar can be explained by the parallel in the amount bioactive components due to cavitation, as reported by Yıkmış et al (2022) [53].…”
Section: Antidiabetic and Antihypertensive Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…The innovation of starter cultures for the improvement of traditional vinegar production is an important biotechnological advancement for vinegar quality and safety [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Their adaptation in diverse environments indicates significant genetic diversity and physiological characteristics. Their adaptation to diverse environments indicates substantial genetic diversity and physiological characteristics, prompting ongoing research into their efficient industrial and food processing applications, including acetic acid production rates, tolerance to acetic acid and ethanol, and high-temperature resistance [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%